The Catch-22 of External Validity in the Context of Constraints to Firm Growth - Fischer, Greg; Karlan, Dean (American Economic Review, 2015)
We document the presence of multiple and varied constraints to small and medium firm growth. This presents both a practical problem for business training programs and a challenge to academic economists trying to identify mechanisms though which these programs may affect outcomes. External validity needs theory. This pushes researchers to narrowly defined and highly selected sample frames, which limits the potential for clear, generalizable policy prescriptions. Ultimately, larger samples, multi-arm evaluations, process documentation, and narrowly-focused, theory-supported empirical work are all needed, but the complexity of the problem limits what we learn from any single study.